Optimizing students' problem-solving ability and learning interest through the educational game "Algebra Explorer: The SPLDV Saga" - Yadi Ardiawan; Rahman Haryadi; Dwi Oktaviana (Jurnal Pendidikan Informatika dan Sains, 2026)
This study aimed to develop the educational game "Algebra Explorer: The SPLDV Saga" and to examine its effectiveness in improving junior high school students' problem-solving ability and learning interest. The study employed the Research and Development (R&D) method following the Borg and Gall model, comprising seven stages: identification of potential and problems, data collection, product design, design validation, product revision, product trial, and evaluation. The subjects were 28 eighth-grade students. The instruments consisted of a problem-solving ability test, a learning interest questionnaire, and a student response questionnaire. Validation results from subject-matter experts (87.47%) and media experts (90.91%) indicated that the product was highly valid and suitable for use. The mean problem-solving score increased from 63.57 to 82.38, and the paired samples t-test yielded a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference between pretest and posttest scores. The N-Gain value of 0.52 (moderate category) demonstrated that the game was effective in improving students' mathematical problem-solving ability, while student responses reached an average of 85.71% (very good category). Therefore, the educational game "Algebra Explorer: The SPLDV Saga" is effective in enhancing students' problem-solving ability and learning interest, and it received highly positive feedback.